Multivariate analysis of GGE and AMMI biplot graph to investigate geno-type by environment interaction of rice hybrids at multiple locations in Malaysia - S., Elixon; Y., Mohd Rafii; R., Asfaliza; J., Mashitah; R., Shairul Izzan (Galaxy Science, 2023)
This study was conducted to investigate the genotype by environment (G×E) interaction of 20 rice hybrids tested in eight environments which include four locations and two different cropping seasons in Malaysia. The parameter was observed on yield per ha, number of panicles per plant, number of filled grains per panicle, and thousand-grain weight. Data analysis was used by ANOVA and stability measurement according to AMMI and GGE biplot graph.  The ANOVA indicated that all studied phenotypic showed significantly different in variance genotypes, season, location, location × season, genotype × season, genotype × location × season.  The most promising hybrids were G19, G3, G18, G13, G8, G7, and G14, resulting in a higher mean yield per ha.  The multivariate stability analysis defined those hybrids divided into three categories. The first category is hybrids with high mean yield and wide adaptability (G19, G18, G3 and G4), the second category is the hybrid exhibiting high mean yield and is suitable for a specific environment (G12) and lastly, a hybrid with low yield and high stability (G9, G11 and G1). Hybrids with high yield and stable performance could be further evaluated in large-scale planting for prior release for commercial.